Oil palm trunk as a raw material for activated carbon production - Hussein, Mohd Zobir; Abdul Rahman, Mohd Basyaruddin; Yahaya, Asmah; Hin, Taufiq-Yap Yun; Ahmad, Nujaimi (Springer, 2001)
Oil palm trunk is a major lignocellulosic-rich, solid waste material generated from palm-oil upstream industry. The activated carbons prepared from oil palm trunk pretreated with phosphoric acid with the ratio of the acid to the precursor of 0.9, followed by carbonization and activation by carbon dioxide resulted in a high surface area of more than 1800 m2/g with 90% content of micropore surface area. The surface area and the nature of the porosity of the resulting activated carbons were found to be dependent on the amount of the activator used for a fixed quantity of the precursor. Pretreatment of the precursor at low ratio of the phosphoric acid has added advantage, due to the tremendous increase in the apparent surface area of the resulting activated carbon and at the same time enriching its micropore nature. This could result in the conservation of the micropore fraction. On the other hand, using too high a ratio of the phosphoric acid to the precursor did not increase the apparent surface area very much, but instead destroyed the micropore component, and thus increasing the mesopore fraction of the resulting activated carbon. This study also shows that oil palm trunk, a by-product of oil palm industry has a great potential as a raw material for activated carbon production.